IMPROVEMENT OF FUNCTIONAL PARAMETERS BY INTRODUCTION MARTIAL ARTS TECHNIQUES IN THE PHYSICAL EDUCATION AND SPORTS LESSONS - Boca Andreea Gabriela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
Tae bo is a combination of martial arts, boxing, and other fitness moves, all performed on music. Tae bo is an aerobic workout beneficial for the cardiovascular and respiratory system. In the present research, we started from the hypothesis that teaching martial arts techniques and combining them with other motor structures, in an aerobic program performed on music, will lead to the improvement of the functional indices of the students from the experimental group. The experiment and control group were made up of 24 subjects (N=24, undergraduated female students), from the Accounting and Management Informatics specialization. The research was carried out during a university semester (14 weeks) and at the end it was shown that the kicks and the punches performed on all trajectories, have had beneficial effects on the cardiovascular and respiratory systems.